Atypical pulmonary manifestation of brucellosis in a non-endemic region: case report from Slovakia - Ondrej Zahornacký; Štefan Porubčin; Alena Rovňáková; Pavol Jarčuška; Katarína Tokarčíková; Diana Horvát Hriseňková (The Egyptian Journal of Internal Medicine, 2026)
Abstract Background Brucellosis is a zoonotic infection with diverse clinical manifestations. Pulmonary involvement is rare—occurring in less than 1% of cases—and typically limited to endemic regions. In Slovakia, where brucellosis is non-endemic, human cases are exceptional. We present a rare and severe respiratory form of brucellosis in a patient with occupational exposure to livestock. Case presentation We describe a 40-year-old female dairy farm worker admitted with fever, chills, and dyspnea. Initial workup revealed mild laboratory abnormalities and chest infiltrates. Despite empirical antibiotics, her condition rapidly progressed to acute respiratory distress syndrome (ARDS), acute kidney injury, and septic shock. Mechanical ventilation and vasopressor support were required. Serological testing confirmed Brucella abortus infection. Antibiotic therapy was escalated to tigecycline and meropenem, with subsequent clinical improvement. Follow-up imaging showed significant regression of pulmonary infiltrates. The patient completed a six-week course of doxycycline and fully recovered. Conclusion This case underlines the importance of considering brucellosis in febrile patients with livestock exposure, even in non-endemic settings. Severe pulmonary forms are rare but life-threatening. Early recognition, targeted antibiotic therapy, and multidisciplinary care are critical for favorable outcomes.